2020
DOI: 10.29089/2020.20.00117
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in women with systemic lupus erythematosus, its association with bone turnover markers, levels of estradiol and interleukin-6

Abstract: Introduction: Osteoporosis is frequently diagnosed in patients with systemic lupus erythematosus (SLE). Potential causes and mechanisms of the development of this disease in patients with SLE are still being studied. Aim: To study bone mineral density (BMD) of women with SLE in Ukraine, evaluate its association with the level of bone turnover markers, interleukin-6 (IL-6) and serum estradiol levels. Material and methods: In total, 91 SLE women and 29 healthy individuals were examined. Apart from clinical ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has been shown that low levels of vitamin D are associated with an increased incidence of osteoarthritis [19], rheumatoid arthritis [20], multiple sclerosis [21], and diabetes mellitus [22]. Active vitamin D and its analogs have been demonstrated to prevent lupus-like symptoms and reduce the development of inflammatory bowel disease [23]. In cases of multiple sclerosis, vitamin D supplementation has been found to decrease proinflammatory cytokines while increasing the release of anti-inflammatory cytokines [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that low levels of vitamin D are associated with an increased incidence of osteoarthritis [19], rheumatoid arthritis [20], multiple sclerosis [21], and diabetes mellitus [22]. Active vitamin D and its analogs have been demonstrated to prevent lupus-like symptoms and reduce the development of inflammatory bowel disease [23]. In cases of multiple sclerosis, vitamin D supplementation has been found to decrease proinflammatory cytokines while increasing the release of anti-inflammatory cytokines [21].…”
Section: Discussionmentioning
confidence: 99%